Experienced Victimization and Confidence in the Police among Young Canadian Adults - Nguyen, Quan (Canadian journal of criminology and criminal justice, 2024)
This article examines how experienced victimization affects the confidence of young adults in the police in Canada. Using data from the 2019 General Social Survey - Cycle 34: Victimizations, our analysis focuses on the subgroup of young adults aged 15 to 34 (N = 3,395). The findings confirm a significant negative correlation between experienced victimization and confidence in the police among young people. Other factors, such as community belonging, neighborhood crime rates, and overall health status, are positively associated with confidence in the police. The results provide insights into how various sociodemographic factors have influenced the perceptions of law enforcement by young adults. The study highlights the challenges faced by Indigenous, vulnerable, and racialized community members (e.g., those with visible minority status, people with disabilities, and those facing discrimination), who often have lower levels of confidence in the police. These findings emphasize the need for comprehensive police-community collaborative strategies prioritizing inclusivity, anti-discrimination measures, and focused support for Canadian young adults to improve their trust and confidence in law enforcement.